Assessing The Authority Of The Village Head Of Buba'a District Of Boalemo Regency Beach District In The Appointment And Dismissal Of Village Devices - Ismet Harun (Universitas Negeri Gorontalo, 2019)
The purpose of this study is to find out how the role of the Village Consultative Agency in supervising the performance of the village head in Buba'a village of Paguyaman Pantai Subdistrict and knowing what factors hinder the supervision of village performance in Buba'a village of Paguyaman Pantai Subdistrict. This research uses normative-empirical research methods with descriptive data analysis techniques with more descriptions of interview results, observations, and documentation studies. The results of this study show that first, the authority of the head of Buba'a Village, Boalemo District Beach District in the appointment and dismissal of village devices has not been by the applicable rules, where for almost three years running in the appointment of village devices recruiting outside communities. This is certainly not by what is mandated by Law No. 6 of 2014 concerning villages. In addition, in the appointment or dismissal of Buba'a Village devices, there is no communication between the village head or the local cat. Second, the factors that hinder the performance of the head of Buba'a Village in the appointment and dismissal of village devices are (1) Factors from within the head of Buba'a Village itself because he ignores the applicable rules; (2) The outside factor as a supporter of the performance of the village head is the function of BPD in monitoring the performance of the village head has not been effective; (3) There is no good 2-way communication between the village chief of Buba'a and the local cat in terms of the appointment and dismissal of village devices.